In Vivo and In Vitro Anti-Hyperglycemic and Hypolipidemic Effect of Atili (Canarium Schweinfurthii) on Streptozotocin Induced Diabetic Rats - Abubakar Ibrahim Garba; Agomuo Jude Kelechi; Nasiru Bilkisu Umar; Idris Zubairu Kaida Kaida; Abubakar Kabir Adam Adam; Maryam Gambo Abdullahi; Saifullahi Abdullahi (Journal of Healthcare and Biomedical Science, 2024)
Canarium schweinfurthii is used as a traditional treatment for diabetes mellitus in Nigeria and other African countries, according to ethnobotanical records. However, scientific evidence has not yet been published. This study aimed to evaluate the antidiabetic effects of Canarium schweinfurthii fruit pulp ethanol extract in streptozotocin-induced diabetic rats. A type II diabetic rat model (TDRM) was established via high-fat diet and Streptozotocin induced diabetes. Diabetic rats were randomized into five different groups; the control group (n = 6) (common diet) and high-fat diet (HFD) groups fed with ethanolic extract at 100, 200, 400, and 600 mg/ml (n = 24). At these doses, the blood glucose was lowered by 57.68% to 80.17%. For hypolipidemic test, total cholesterol was lowered from 162.33 mg/dL to 70.19 mg/dL; Glyceride from 166.91 mg/dL to 68.61mg/dL. Creatinine from 6.77 mg/dL to 6.42 mg/dL. Alanine Aminotransferase was 151.3 to 53.31 µI/L in 600mg group. Aspartate Aminotransferase enzyme decrease from 130.4 µI/L to 40.81 µI/L. This study confirmed the antidiabetic effects of Canarium schweinfurthii fruit extract.